Mindful English: Incorporating SEL (Social Emotional Learning) into Language Teaching - Murodova Rukhsora (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This article conducts a thorough analysis of the integration of Social and Emotional Learning (SEL) within the realm of language education, highlighting its significant impact on enhancing learner motivation, building confidence, developing communicative competence. By examining the interplay between emotional intelligence and language acquisition, we can uncover how SEL strategies can be effectively employed to create a more holistic educational experience. The importance of fostering a supportive learning environment can not be overstated, as it directly influences students’ willingness to engage with the material and participate in communicative activities. Furthermore, the incorporation of SEL principles helps to build a foundation of self-awareness and interpersonal skills, which are essential for effective communication in any language. Additionally, this paper comprehensively examines the limitations encountered during implementation, specifically highlighting critical factors such as time constraints, cultural considerations, and the complexities associated with assessment.